Emergence and Comparative Genomics Analysis of Extended-Spectrum-β-Lactamase-Producing Escherichia coli Carrying mcr-1 in Fennec Fox Imported from Sudan to China - Chunyan Feng (American Society for Microbiology, 2019)
ABSTRACT The aim of this study was to investigate the occurrence and genomic characteristics of extended-spectrum-β-lactamase-producing Escherichia coli (ESBL-EC) in fennec fox imported from Sudan to China. We screened 88 fecal samples from fennec fox for ESBL-EC, using cefotaxime- and meropenem-supplemented selective medium. Antimicrobial susceptibility testing was performed by the agar dilution method except for colistin and tigecycline; for colistin and tigecycline, testing was conducted by the broth microdilution method. ESBL-EC bacteria were sequenced, and their genomes were characterized. Plasmid conjugation, S1 nuclease pulsed-field gel electrophoresis (PFGE), and Southern blotting were performed for a MCR-1-producing isolate. The genetic environment of mcr-1 and ESBL genes was also investigated. A total of 29 ESBL-EC bacteria were isolated from 88 fennec fox (32.9%), while no carbapenemase producers were found. The most prevalent genotypes were the blaCTX-M-55 and blaCTX-M-14 genes, followed by blaCTX-M-15 and blaCTX-M-64. We detected nine sequence types among 29 ESBL-EC. Furthermore, the mcr-1 gene was detected in isolate EcFF273. Conjugation analysis confirmed that the mcr-1 gene was transferable. S1 PFGE, Southern blotting, and whole-genome sequencing revealed that mcr-1 and blaCTX-M-64 were both located on a 65-kb IncI2 plasmid. This study reports for the first time the occurrence of ESBL-EC in fennec fox. The high prevalence of ESBL producers and the occurrence of MCR-1 producer in fennec fox imported into China from Sudan are unexpected. In addition, it clearly demonstrated that commensal E. coli strains can be reservoirs of blaCTX-M and mcr-1, potentially contributing to the dissemination and transfer of such genes to pathogenic bacteria among fennec fox. Our results support the implication of fennec fox as a biological vector for ESBL-producing members of the Enterobacteriaceae family. IMPORTANCE The extended-spectrum-β-lactamase (ESBL)-producing members of the Enterobacteriaceae family are a global concern for both animal and human health. There is some information indicating a high prevalence of ESBL producers in food animals. Moreover, there have been an increasing number of reports on ESBL-producing strains resistant to the last-resort antibiotic colistin with the global dissemination of the plasmid-mediated mcr-1 gene, which is believed to have originated in animal breeding. However, little is known regarding the burden of ESBL-producing Enterobacteriaceae on wild animals. No data were available on the prevalence of antimicrobial resistance (AMR) among wild animals imported into China. This is the first study to investigate the microbiological and genomics surveillance investigation of ESBL colonization among fennec fox (Vulpes zerda) imported from Sudan to China, and we uncovered a high prevalence of ESBL-EC. Furthermore, the underlying mechanism of colistin resistance in an isolate that harbored mcr-1 was also investigated. Results of characterization and analysis of 29 ESBL-producing E. coli may have important implications on our understanding of the transmission dynamics of these bacteria. We emphasize the importance of improved multisectoral surveillance for colistin-resistant E. coli in this region.